Alternative Agricultural Cropping Options for Chlordecone-Polluted Martinique - Alfred Wong; Christine Ribero (Études Caribéennes)
Martinique is currently beset by, among other things, chronic high unemployment rate and steadily rising cost of food and other life essentials. Overlaying this societal problem is the continuing ecological disaster of chlordecone contamination of about 1/3 of the land surface, and surrounding waters. Chlordecone is extremely toxic and recalcitrant; its use was banned in the USA in 1979, but it was used continually until 1993. Alternative agriculture is a practicable means to alleviate the deep social unrest arising from chronically high unemployment rate and near total dependency on costly food imports from metropolitan France. One of the basics aims of this approach would be the zero use of synthetic chemicals for pest-and weed-control for all crops. Cropping of certain edible Solanaceae fruits, viz, bell pepper, appears to be feasible under a semi-open greenhouse environment, in which natural sunlight, rainfall and warm year-round temperatures would be deployed maximally. The carbon footprint of this prospective Martinique produce delivered to the UK might be substantially lower than that of bell peppers grown in stand-alone heated greenhouses in mainland Europe.